0378 Occupational exposure to carcinogens in New Zealand. (23rd June 2014) - Mannetje, Andrea't; McLean, David; Glass, Bill; Cheung, Kerry; Douwes, Jeroen; Pearce, Neil
Abstract : Objectives: To provide a detailed assessment of the extent and industrial distribution of workplace carcinogens in New Zealand, and to identify key industries and key carcinogens for which intervention would result in marked reductions in occupational cancer. Method: A literature review was conducted identifying the carcinogens present in and the cancer risks associated with each respective industry. A New Zealand specific Information System on Occupational Exposure to Carcinogens (NZ-CAREX) was developed. Results: There are more than 50 known human carcinogens commonly present in New Zealand workplaces. The most common of these are: asbestos; benzene; chromium VI compounds; formaldehyde; involuntary smoking; occupational exposures as a painter; silica; solar radiation; wood dust. The industries for which an increased cancer risk has been observed repeatedly in epidemiological studies and have the highest number of potentially exposed workers include: agriculture; construction; health services; machinery and equipment manufacturing; metal product manufacturing; and wood/paper product manufacturing. Of the agricultural chemicals currently in use in New Zealand's agricultural sector, none are known human carcinogens, but numerous are suspected to be carcinogenic to humans. A number of barriers for the implementation of intervention strategies were identified, which could be removed by improving access to knowledge regarding the occurrence of carcinogens in New Zealand workplaces and improving access to control tools and methods to evaluate their effectiveness. Conclusions: Exposure to carcinogens remains common in New Zealand workplaces, and many opportunities remain for reducing exposure and the associated occupational cancer burden.